An Unusual Case of Ventricular Tachycardia in a Young Patient Associated with Cannabis Use - Sampat, Parth J. (Case Rep Cardiol, 2020)
Marijuana has become the most widely used illicit drug in the United States. Approximately 43.5 million Americans aged 12 or above have reported the use of marijuana in the last year. The use of cannabinoids and its relationship with cardiac effects are not well known. Many types of arrhythmias have been noted with the use of cannabis products with atrial fibrillation being the most common arrhythmia associated with the use of cannabis. We present a case of a 36-year-old male who presented with pounding chest pain, dyspnea, and diaphoresis following marijuana use. He was found to be in ventricular tachycardia which responded to amiodarone. Workup done was negative for any structural disease, and cardiac catheterization was negative for coronary artery disease. He was ultimately discharged on metoprolol. In this report, we focus on how marijuana can be associated with many arrhythmias including ventricular tachycardia with focus on mechanisms by which it can occur. We believe a detailed social history with screening for cannabis use can identify more cases of arrhythmias that can be potentially associated with marijuana use.